Assessing the implementation of joint programming in government social protection and economic inclusion interventions in the Philippines - Jose Ramon G. Albert; Frances Genevieve F. Genio; Jan Joy Louise G. Crismo (Philippine Institute for Development Studies (PIDS), 2025)
Joint programming, also referred to as convergence, in social protection and economic inclusion interventions has emerged as a critical strategy for addressing persistent poverty in the Philippines. Despite the government's ambitious target to reduce poverty from 18.1% in 2021 to 9% by 2028, significant challenges remain in coordinating and integrating social protection efforts. This study examines the implementation of joint programming across laws, policies, and programs targeting Filipinos living in poverty. Using an approach with emphasis on qualitative data, the research assesses the current state of joint programming, identifies key stakeholders, evaluates implementation challenges, and analyzes the effectiveness of existing coordination mechanisms. Through document analysis, key informant interviews with government officials and field staff, and focus group discussions with program beneficiaries, this study aims to provide actionable recommendations for enhancing joint programming efforts. The findings are expected to contribute to the refinement of social protection and economic inclusion strategies in the Philippines, ultimately supporting the government's poverty reduction goals and improving the lives of vulnerable populations.
Keywords: 330; joint programming; convergence; social protection; economic inclusion; poverty reduction